2017
DOI: 10.1161/strokeaha.117.016893
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care for Hospitalized Patients With Stroke

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…US-based research has consistently found that women are more likely than men to be enrolled in hospice which is seemingly related to both provider and patient bias. 65 69 Saeed and colleagues 67 found that, among 383 patients with metastatic cancer, women were three times more likely than men to consider palliative care, even when controlling for disease factors, age, race, education and financial strain. The study authors explained the results as follows: there is a societal norm that men are supposed to be tough and invulnerable and there is a lot of vulnerability in seeking help and focusing on comfort care instead of always being in fighter mode.…”
Section: Gender and Hospice And Specialist Palliative Carementioning
confidence: 99%
“…US-based research has consistently found that women are more likely than men to be enrolled in hospice which is seemingly related to both provider and patient bias. 65 69 Saeed and colleagues 67 found that, among 383 patients with metastatic cancer, women were three times more likely than men to consider palliative care, even when controlling for disease factors, age, race, education and financial strain. The study authors explained the results as follows: there is a societal norm that men are supposed to be tough and invulnerable and there is a lot of vulnerability in seeking help and focusing on comfort care instead of always being in fighter mode.…”
Section: Gender and Hospice And Specialist Palliative Carementioning
confidence: 99%
“…Four studies, using medical chart reviews, found that there were no racial differences in rate of inpatient palliative care consult (Bhatraju, Friedenberg, Uppal, & Evans, 2014;Burgio et al, 2016), time to inpatient palliative care consult (Worster et al, 2018), or use of outpatient palliative care services (Kumar et al, 2012). However, three studies using the NIS, a nationwide, population-based database of inpatient care in the United States, found that minority patients received fewer palliative care services (Faigle et al, 2017;Rush et al, 2017;Singh et al, 2017). Two studies, examining the rates of palliative care use in cancer patients, found that African American patients actually received more palliative care services than white and other minority patients (Rosenfeld et al, 2018;Sharma et al, 2015).…”
Section: Disparities In Palliative and End-of-life Carementioning
confidence: 99%
“…This set off a cascade of initiatives aimed at increasing PC utilization by augmenting PC certification among surgeons, encouraging PC specialist referrals, and providing education about palliative treatment strategies in daily surgical practice. [79,11–17]…”
Section: Discussionmentioning
confidence: 99%
“…[4547] Hospitals that were academic, not-for-profit, and of larger bedsize also had higher rates of use, consistent with multiple prior studies showing higher prevalence of PC programs, and naturally higher utilization of PC, in hospitals with these same features. [17,18,23,44,45]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation